Cost evaluation of the Merlin assay for predicting melanoma sentinel lymph node biopsy metastasis. (28th November 2022) - Thao, Viengneesee; Dholakia, Ruchita; Moriarty, James P.; Borah, Bijan J.; Dwarkasing, Jvalini; Meves, Alexander
Abstract: Background: The Merlin assay for melanoma‐risk assessment has become commercially available to reduce the rate of unnecessary sentinel lymph node biopsies (SLNB) in SLNB‐eligible patients with cutaneous melanoma. Merlin low‐risk patients are recommended to undergo wide local excision (WLE) of the primary tumor, whereas Merlin high‐risk patients are recommended to undergo both SLNB and WLE. Here, we compared the cost of a Merlin testing strategy to that of a no‐testing strategy (usual care) before prescribing SLNB. Methods: We identified T1 and T2 patients who underwent WLE and SLNB but not completion lymph node dissection between 2007 and 2018. Controls were T1 patients who only underwent WLE. Costs for WLE and SLNB were calculated by converting institutional cost data to standardized Medicare reimbursement rates. We then developed a decision tree to compare the cost of Merlin testing to that of a no‐testing strategy (usual care). Results: The average standardized cost of WLE was $2066, whereas the cost of WLE and SLNB was $11, 976 based on Medicare rates. At a cost below $7350 for T1b melanoma and $4600 for T1b to T2 melanoma, Merlin testing was cost‐saving compared to a no‐testing strategy (usual care), assuming Medicare reimbursement rates. Conclusion: Merlin testing for T1b and T2 melanoma is potentially cost saving depending on the cost of the molecular assay and SLNB reimbursement rates. In addition to being cost saving, Merlin is expected to improve health‐related quality of life.